Biological age in the physical preparation of athletes of Artistic Gymnastics in Pinar del Río - Mercedes Miló Dubé (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
Sport initiation of athletes should start from a base orientation of multilateral physical preparation adapting training to the ages of the children, in this process is important to have in mind the biological age as main element in the development of physical capacities for the organization and forecast of their performances against chronological age as is structured in the programs of preparation for athletes. This research has the objective of incorporate the criterion of biological age to the process of physical preparation of athletes of artistic gymnastics in the category 11-12 years at the sports initiation school in Pinar del Río. A total of 55 girls were selected in the category 11-12 years of artistic gymnastics, their biological age was determined by Tanner Wuitehouse method, which consisted in the X-ray evaluation of bone maturation of the bones of the hand of the girls athletes, a total of 35 specialists were interviewed who work at the different sports centers in the province of Pinar del Río. We determined the means, standard deviation, variation rate and percentage analysis to obtain the reliability and objectivity of the obtained results. The increase or decrease of work capacity, its systematic evaluation through the application of a test specifically oriented to such a degree in the practice results in a formal routine and not an instrument employed in the management and control of training process.Besides, the accepted concept of biological age,does not have any application in the planning of training of the athletes subject of our research, which could be caused by the inadequate development of the different capacities which should constitute the essence of preparation of the athlete at this age.